(untitled) (Majalah Kedokteran Bandung, 2021)
One of common heavy metals that pollute rivers in Indonesia is copper, which can damage various organs, including the lungs. As a potential natural herbal medicine, white turmeric rhizome has antioxidant properties that potentially protect the body from copper pollution. This study aimed to explore the potential of the white turmeric rhizome (Curcuma zedoaria) to provide a protective effect on the lungs against copper contamination. This study was an experimental study performed in June 2020 on 25 copper-induced Wistar rats which were divided into five groups: negative group that received 1 ml of copper sulfate suspension at the 12th to 14th day; positive group that received 10 mg/200 g BW of ethanol extract from white turmeric without copper sulfate suspension; and three experimental groups that received 10 mg/200 gBW, 20 mg/200 gBW, and 40 mg/200 gBW of ethanol extract from white turmeric every day, respectively, followed by copper sulfate suspension at the 12th–14th day. After 14 days, the rats were sacrificed by chloroform inhalation and the lung was excised and processed for histopathology preparation. The edema, hemorrhage, leukocyte infiltration, and alveolar septal thickness were evaluated from the lung tissue perparation. The score of tissue damage was express as median (Range) and analyzed using the Kruskal-Wallis test. The result of this study shows that there was a significant difference in lung tissue score among all groups of treatment (p-Value=0.001). The experimental group with highest dosage extract presented a good protection effect as well as the positive group. Hence, white turmeric has a good protective property for the lung against damages caused by copper contamination.